Plastic pellets along Kuala Selangor-Sepang coastline. - Ismail, Ahmad; N.M.B., Adilah; M.J., Nurulhudha (Malaysian Society of Applied Biology, 2009)
Plastic pellets are considered as marine debris pollutants (Gregory, 1977). They can be defined as small granules or raw materials that will be melted and molded into plastic products that can be found stranded on the beaches all over the world. It has several shapes and colors. Their shapes are in the form of tablet, oblong, cylindrical, spherical and disk shape, whereas the color are white including clear and transparent, black, blue, yellow, purple, red, green, brown, grey and pink. Usually, plastic pellets (Fig. 1) can be found in the environment due to the spillage during shipping loading and unloading. Since, plastic pellets are made of plastic, which is primary synthetic organic polymer derived from petroleum. Therefore, when it is exposed to UV radiation in sunlight and water from the ocean, this polymer will break into smaller pieces. This process will take time to occur naturally.